First report of grapevine Roditis leaf discoloration-associated virus infecting grapevine in Argentina - Cuello, Raul Andres; Debat, Humberto Julio; Zavallo, Diego; Lanza Volpe, Melisa; Prieto, Jorge Alejandro; Torres, Maria Del Rocio; Gomez Talquenca, Gonzalo; Asurmendi, Sebastian (Springer, 2025)
Grapevine Roditis leaf discoloration-associated virus (GRL DaV) is a monopartite DNA virus belonging to the genus Badnavirus (family Caulimoviridae). GRLDaV is associ ated with yellow and/or reddish leaf discoloration symp toms and may compromise grapevine health and reduce productivity (Maliogka et al. 2015). This virus, transmitted by the vine mealybug Planococcus ficus (Ulubaş-Serçe et al. 2024), has previously been reported in Europe and South Africa (Bester et al. 2021) but has not yet been identified in the Americas.